Legal Politics and Compliance in Forming Village Budget Regulations - Yeni Fera Anggraini; Diyan Isnaeni; Novi Sri Utami (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Village autonomy in Indonesia, as regulated in Law No. 6 of 2014 and refined in Law No. 3 of 2024, grants villages significant authority to manage their governance and finances through the Village Revenue and Expenditure Budget (APBDes). Specific Background: However, the drafting of village regulations often diverges from positive law, revealing tension between national legal ideals and local political practices. Knowledge Gap: Few studies comprehensively analyze how national legal politics and local compliance interact in shaping legally accountable village governance. Aims: This study aims to analyze the influence of legal politics and compliance with positive law in the formation of village regulations on APBDes. Results: Using a normative juridical method with legislative, conceptual, and sociological approaches, the study finds that compliance with positive law is strongly determined by central legal politics, human resource capacity, and village legal culture. Decentralization has increased autonomy but also introduced risks of legal deviation. Novelty: This research integrates the concept of legal politics with village-level compliance analysis, positioning legal awareness as a moral and structural foundation of governance. Implications: Strengthening legal culture and supervision mechanisms is essential to ensure that village regulations reflect justice, transparency, and public interest rather than local political interests. Highlights: Legal politics directs village regulation formation within the national legal framework. Compliance with positive law depends on human resources and legal culture. Strengthening supervision ensures justice, transparency, and accountability in governance. Keywords: Legal Politics, Positive Law, Village Regulations, APBDes, Legal Compliance